Development of Web-Based Project Tender Documents Application Using Extreme Programming Methods - Mustari Lamada; Aminuddin Bakry; Aulyah Zakilah Ifani; Khaerunnisa Khaerunnisa (Department of Electronic and Informatic Engineering Education, Faculty of Engineering, UNY, 2022)
The application of technology is a need that is in demand in the industrial world today, especially in the field of contractors of goods and services that have implemented the use of applications to help the process of managing data and project documents in their companies. This study aims to optimize the web-based project tender document system using the extreme programming method. The extreme programming method consists of planning, design, coding, testing, and software increment. Research methods using extreme programming methods consisting of planning, design, coding, testing, and software increment. The planning stages obtain results in the form of functional and non-functional application needs. The design stage results in the design of applications using activity diagrams, diagram classes, use case diagrams, and flowcharts. The coding stages obtain results in the form of applications that can be built using web programming languages. The testing stage uses the ISO 9126 standard. Suitability test results are worth 1 (very good), security is not found to have viruses or malicious malware in applications (grade B), reliability is worth 0.99 (good), usability is worth 90.9% (very feasible), efficiency is worth 98% (grade A), maintainability meets the three standard aspects of assessment (good), and portability is worth 1 (very good). The software increment stage obtained results in the form of implementation and application trials on users who have functioned properly. Based on the results, it can be concluded that the development of web-based project tender document applications using extreme programming methods can function properly and be feasible to use.